Evaluation of the antagonistic and plant growth promoting properties of Streptomyces isolated from aubergine rhizosphere soil of Kanchipuram, Tamil Nadu, India - Yogesh Pradeep, L.; Masilamani Selvam, M.; Manigundan, K.; Gopikrishnan, V.; Radhakrishnan, M.; Jerrine, J.; Soytong, K. (International Journal of Agricultural Technology, 2021)
The actinobacteria were isolated from the rhizosphere soil and characterized its plant growth promotion and antagonistic ability against Ralstonia solanacearum. Totally seven actinobacteria strains were isolated from aubergine rhizosphere soil and their cultural and morphological characterization showed all the seven strains belongs to Streptomyces spp. In vitro antagonistic screening of actinobacteria against R. solanacearum showed over 20 mm zone of inhibition by KTR3, KTR-4 and KTR6. Similarly, KTR-3 and KTR-4 produced the maximum level of IAA. In addition, the highest level of ammonia produced by KTR-6 and KTR-3. Among these seven strains, KTR-3 is alone able to produce IAA, siderophore, ammonia, cellulase, amylase and protease and solubilized phosphate. Also, in planta study showed 100% seed germination and highest shoot and root length in tomato, aubergine and chili which higher than other treatments. The strain KTR-3 was expressed the highest antimicrobial activity against R. solanacearum on utilization of glucose (24mm), peptone (24mm), ferrous sulfate (15mm) and pH 7 (23mm) as different sources. It exhibited the potential plant growth promoting and antagonistic activities, Streptomyces strain KTR-3 would be a promising candidate for agricultural use